Cracked Tooth Syndrome: Clinical Diagnosis, Nursing Care, and Laboratory Considerations. - Almutairi,YousefMohammadGh; Al-Asmari, Noura Jaber; ALruwaili, Hanan Zaal R; Al Saadi, Huda Daifallah; Almutairi, Mohammed; ALRushaidan, Khalid Fahd Ali; ALNoman, Abdulaziz Fouad Abdulqader; Alruwaili, Asala Hamdan; Alabbad, Fatimah Mohammed Eisa; Alghamdi,SalehMohammed; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Cracked tooth syndrome (CTS) is a prevalent, diagnostically challenging condition with heterogeneous symptoms and variable progression that can compromise pulpal and periodontal health. Aim: To synthesize contemporary clinical guidance on CTS encompassing diagnosis, nursing care, and laboratory considerations to inform patient-centered, team-based management. Methods: Narrative integration of clinical history/physical examination features, adjunctive diagnostic tools (magnification, fibreoptic transillumination, bite tests, vitality testing, radiography/CBCT), etiologic and epidemiologic determinants, treatment pathways from conservative stabilization to endodontic therapy or extraction, and interprofessional roles. Results: Early, structured evaluation improves localization and staging of cracks and enables timely stabilization. Direct bonded restorations and provisional external splinting relieve symptoms and reduce flexure; definitive cuspal coverage redistributes occlusal forces. Pulpal involvement or root extension worsens prognosis and may necessitate endodontic treatment with guarded long-term survival or extraction. Nurses augment outcomes through triage, education, and adherence support; laboratories optimize material selection, digital design, and splinting biomechanics. Conclusion: CTS outcomes improve when clinicians pair rigorous diagnostics with staged biomechanical control and clear expectation-setting, supported by coordinated nursing and laboratory contributions. Early detection remains the pivotal determinant of tooth preservation.